Building resilience for food systems in postwar communities case study and lessons from northern Sri Lanka - Pathmanathan, Hamsha; Babu, Suresh Chandra; Pal, Chandrashri (International Food Policy Research Institute, 2017)
Prolonged civil wars can have long-lasting adverse effects on food systems, leading to poverty and food insecurity. Overcoming food insecurity and land inequality is particularly difficult because of the highly politicized nature of conflict. This paper builds on the existing literature on food sovereignty to ensure sustainable livelihoods and community ownership of a resilient food system. We identify components of community food security to be strengthened in a post war reconstruction context. We study the impacts of the civil war on food and land administration systems, farmer struggles and current transitional justice process in relation to community food security in the Northern and Eastern Provinces in Sri Lanka and identify the technological, institutional, organizational, and infrastructural setbacks caused by conflict. It explores how such setbacks could be rectified and a resilient food system could be built in the postwar scenario.